A Comparative Study of Practice Ability Development Motivation and Curriculum Adaptation for Advanced Business English Learners in a Chinese University - Qing Xie (SAGE Open)
This study reports on an investigative study with 70 English majors and 39 non-English-majors in a Chinese university who were recruited using convenience sampling, on their practice ability development motivations and needs, the effectiveness of business English curriculum in practice ability development and practice-oriented curriculum adaptation suggestions, based on two-stage surveys and teacher’s participant observation. The study results generated from numerical theme calculation and response content analysis showed that although the non-English-majors were more motivated than the English-majors, both groups had an intermediate level of practice-oriented motivation. Most English-majors and non-English-majors considered the business English curriculum as effective in enhancing their practice abilities. Regarding curriculum adaptations and post-course activities, most English-majors and non-English-majors encouraged more simulation-based practice and group activities, and the integration of diverse business and trade language and knowledge development activities. The results and research process of the study can inform future research on business English curriculum development.